Penegakan Hukum terhadap Pelanggaran Penggunaan Telephone Selular saat Berkendara - I Putu Raditya; Ida Ayu Putu Widiati; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2020)
Cellular Telephone is a communication tool that can connect people with others who are obstructed by distance and time. Its use is now a priority for most people. The level of traffic accidents caused by drivers who drive their vehicles while using the telephone is also increasing. In connection with the above it will be discussed regarding the regulation of the use of cellular telephone while driving as well as law enforcement for motorists who violate the use of cellular telephone while driving. In this paper the method used is a normative legal method which uses legal material collection techniques in the form of study documents and uses primary legal material sources such as legislation and secondary legal materials such as legal books which are then poured descriptively to get final conclusions. Then regarding the conclusions of the results of this study namely violations of the use of cellular telephones have explained that in driving there is no concentration to cause an accident and even to cause death then threatened with imprisonment and fines as regulated in Law No. 22 of 2009 concerning Past Road Traffic and Transportation. For law enforcement efforts to prevent the use of cellular telephones it is necessary to understand the community from adolescents to adults of the dangers and impacts of using cellular telephones when driving. So that safety can be created in driving with other public road users.